Identification of an Aptamer With Binding Specificity to Tumor-Homing Myeloid-Derived Suppressor Cells - Tian, Shaohui; Welte, Thomas; Mai, Junhua; Liu, Yongbin; Ramirez, Maricela; Shen, Haifa (Frontiers in Pharmacology, 2022)
Myeloid-derived suppressor cells (MDSCs) play a critical role in tumor growth and metastasis. Since they constantly infiltrate into the tumor tissue, these cells are considered as an ideal carrier for tumor-targeted drug delivery. We recently identified a DNA-based thioaptamer (T1) with tumor accumulating activity, demonstrated its potential on tumor targeting and drug delivery. In the current study, we have carried out structure-activity relationship analysis to further optimize the aptamer. In the process, we have identified a sequence-modified aptamer (M1) that shows an enhanced binding affinity to MDSCs over the parental T1 aptamer. In addition, M1 can penetrate into the tumor tissue more effectively by hitchhiking on MDSCs. Taken together, we have identified a new reagent for enhanced tumor-targeted drug delivery.